Quantification and Assessment of Sustainable Urban Mobility Development in Selected EU Countries Using a Composite Index - Antczak, Elżbieta; Wiaderny, Łukasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
The paper quantifies and assesses the level of sustainable (green) urban mobility development in selected countries of the European Union. For this purpose, key indicators describing different areas of green transport in the years 2011–2020 were constructed. The analysis used available public data and applied Hellwig’s dynamic taxonomic method. The results of the analysis made it possible to answer the following research questions: 1) “What is the status and dynamics of green transport development in the countries studied?”, 2) “Which countries in the EU are leaders in sustainable transport and why?”, 3) “What determines the differentiation and development of green urban mobility in the countries studied?”. The results of the study show that, despite the spatial polarisation of development, there is a structural similarity that characterises the countries with the highest and lowest levels of sustainable mobility development. A strong group is formed by the Scandinavian countries, Belgium (the leader), Hungary, Austria, Denmark, and the Czech Republic. In the years 2011–2020, a decline in the level of development in the sustainable transport sector can be observed, caused, among others, by the effects of the global financial crisis in the years 2011–2014. In contrast, the years 2015–2020 brought a dynamisation of the growth of green transport. Analysing the determinants of this development, it can be noted that, despite the efforts made, European transport policy still faces many challenges, especially due to the steady increase in greenhouse gas emissions in this sector. In addition, regional specificities and differences in transport models risk undermining the results of the European Union’s efforts in this field.